Gemeinsam Karriere machen Die Verflechtung von Berufskarrieren und Familie in Akademikerpartnerschaften - Rusconi, Alessandra; Solga, Heike (Verlag Barbara Budrich, 2011)
More and more women are pursuing a career, and the vast majority of women with a career (inside and outside academia) have a partner who is also pursuing a career. This poses many questions: What does it mean that the careers and lives of highly qualified women and men are intertwined in couples' lives? What new challenges does this pose for women's careers on the one hand and for coordination arrangements in partnerships on the other? Do different ways of interweaving exist in different stages of life or occupational phases?